E-commerce and price setting: Evidence from Europe - Georg Strasser; Elisabeth Wieland; Pawe± Macias; Aneta B±açzejowska; Karol Szafranek; David Wittekopf; Jörn Franke; Lukas Henkel; Chiara Osbat (European Central Bank (ECB), 2023)
E-commerce has become more prevalent throughout Europe in the last decade. The coronavirus (COVID-19) pandemic accelerated this trend, particularly in the retail sector. This paper focuses on the implications of increasing business-to-consumer ecommerce for prices and inflation in the euro area. It highlights three key results. First, whether online prices and inflation are higher or lower than their offline counterparts depends on the distribution model, the sector and the country. Moreover, properly selected online prices track official inflation indices even in real time. Second, the effect of e-commerce on inflation appears to be transient and differs between countries. However, as the penetration of some markets is still low, these transitory effects will likely persist at the euro area level for several years. Third, online prices change more frequently than offline prices. This might lead to greater price flexibility overall as online trade gains market share in a growing number of sectors.
Keywords: D4; E31; L11; 330; e-commerce; price rigidity; inflation; consumer prices; microdata